ANALYSIS OF EFFECTS OF APP PERMISSION CONCERNS ON INTENTIONS TO DISCLOSE PERSONAL INFORMATION: A CASE STUDY OF MONEY TRANSFER SERVICE APP - Azis Amirulbahar; Yova Ruldeviyani (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2023)
Data growth increased alongside the rise of mobile app users in financial services. In Indonesia, the number of financial services application downloads reached 24 million by the end of 2022, with a 28.72 percent increase in transactions. However, this growth also brings issues regarding the potential misuse of personal information, although according to the Personal Data Protection Act (UU PDP) in Indonesia, personal data is protected and kept confidential when accessed by another party. This prompts users to be more cautious in disclosing personal information. On the other hand, users are faced with risks to personal data that can be accessed by service providers, one of which is through app permissions. This research focuses on the influence of App Permission Concerns on users' intentions to disclose their personal information, with a case study of a money transfer services app in Indonesia, namely Flip, that received numerous negative reviews about users' data privacy concerns, especially when verifying using an identity card. The study uses a quantitative approach with PLS-SEM for data analysis. Convenience sampling was used, and data were collected via a questionnaire distributed through Google Forms on social media from May 9 to May 21, 2023 and a total of 224 respondents were obtained. The results of this study indicate that App Permission Concerns have a significant influence on Privacy Fatigue, Privacy Awareness, Privacy Concern and Trust. Trust significantly influences Intention to Disclose. This research is expected to contribute to future studies on app permissions and mobile app feature development.